Treatment of graft-versus-host disease with monoclonal antibodies and related fusion proteins. Issue 5 (October 2010) - Schroeder, T; Haas, R; Kobbe, G
Allogeneic hematopoietic stem cell transplantation has evolved from an experimental treatment approach to a widely used, curative therapy to treat malignant and nonmalignant diseases of the hematopoietic system. Despite advances in donor selection, conditioning regimens and supportive care, acute and chronic graft-versus-host disease (GvHD) remain a major cause of morbidity and mortality. Steroids are the standard first-line treatment and are able to control GvHD in approximately 50% of patients. Those who fail on steroids have a poor long-term prognosis. Therefore, a large number of drugs and procedures have been evaluated as second-line therapy. Monoclonal antibodies have increasingly been used to treat malignancy and autoimmune disease during the last 20 years. Their unique ability to target specific antigens theoretically enables them to directly interfere with cellular mechanisms that are involved in GvHD pathology. For this reason, monoclonal antibodies have been studied extensively as a second-line treatment for acute and chronic GvHD. The purpose of this article is to collect published data on clinical trials from the current literature and to give an overview on efficacy and toxicity of monoclonal antibody treatment for GvHD.